A method for preparing a high temperature resistant lightweight composite ceramic heat insulation screen
Treatment of glass fiber cloth and charcoal fiber cloth through modification and impregnation, and make high temperature firing to form a ceramic-C/C composite material, which solves the poor deformation and corrosion resistance of the existing C/C thermal field at high temperature at high temperature. The problem realizes large -scale, high -intensity and long -life thermal insulation screens, reducing costs and improving industrial benefits.
Patent Information
- Application Number
- CN202210090503.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-01-25
AI Technical Summary
Existing C/C thermal field structural parts are prone to deformity at high temperatures, have poor corrosion resistance, short service life, and large-scale production leads to tight carbon fiber resources and rising costs, affecting the photovoltaic materials industry.
The method of preparing light-quality composite ceramic insulation screens can be modified and impregnated by the glass fiber cloth and charcoal fiber cloth, and the ceramic-C/C composite material is formed through high temperature firing performance.
A large -scale, high -intensity thermal insulation screen has been achieved, the manufacturing cost is reduced, the service life is prolonged, the amount of charcoal fiber uses the amount of charcoal fiber, and improved the economic benefits and production efficiency of the photovoltaic material industry.
Smart Images

Figure BSA0000264733620000021 
Figure BSA0000264733620000031 
Figure BSA0000264733620000032
Abstract
Description
Technical field:
[0001] The invention relates to the field of high temperature resistant materials, and in particular to a method for preparing a high temperature resistant lightweight composite ceramic heat insulation screen. Background technology:
[0002] With the implementation of the national policy of developing new energy solar photovoltaic power generation, the photovoltaic power generation material single (multi) crystal silicon material industry has developed rapidly, and the demand for C / C thermal field structural parts has increased significantly. The heat shield is an important thermal field structural part of the single crystal furnace, and the demand is very large. It is made of carbon fiber and prepared by chemical vapor deposition (CVD). However, with the development of single crystal furnaces towards large-scale and continuous crystal pulling technology (single crystal pulling time is greater than 240 hours), new and higher requirements have been put forward for the performance of the heat shield and its preparation technology, and the conventional C / C thermal field structural parts prepared by the aforementioned CVD method can no longer meet the current demand. At the same time, the existing C / C thermal field structural parts still have several defects. First, it is difficult to prepare large-sized thin-walled cylindrical structural parts by the preform CVD method; second, the structural parts of C / C materials are easy to deform under long-term high temperature, have poor corrosion resistance, are easy to pulverize, and have a low service life; third, there are currently 30,000 to 50,000 single crystal furnaces in my country and under construction, and 90,000 to 150,000 C / C heat shields installed. Such a large number requires 3,000 to 5,000 tons of carbon fiber. If the service life of the C / C heat shield is reduced, the update volume is also very huge. At the same time, the high price of carbon fiber and the shortage of domestic resources have led to an increase in the price of C / C heat shields, which is an obstacle to the photovoltaic material industry. In addition, the frequent replacement of C / C thermal field structural parts also has a huge impact on production efficiency. Therefore, the problem of thermal field structural parts used in single crystal furnaces needs to be solved. Summary of the invention:
[0003] The invention aims to disclose a method for preparing a high temperature resistant and corrosion resistant lightweight composite ceramic heat insulation screen.
[0004] The technical solution of the present invention is: the steps of the preparation method of the high temperature resistant lightweight composite ceramic heat insulation screen are as follows:
[0005] a. Preparation of a colloidal modifier for glass fiber cloth, the glass fiber cloth is immersed in the colloidal modifier and then taken out, and baked at 100 ℃ ~ 110 ℃ to obtain a modified prepreg of glass fiber cloth;
[0006] b. preparing an impregnation liquid for a carbon fiber cloth, impregnating the carbon fiber cloth in the impregnation liquid, taking it out, covering it with a high temperature resistant plastic film, and heating it at 100 ℃ to 120 ℃ to obtain an impregnated carbon fiber cloth;
[0007] c. Laminating multiple layers of the modified prepreg to form a modified prepreg blank, and heating and curing the blank;
[0008] d. The modified prepreg and the impregnated carbon fiber cloth are alternately laminated to obtain a laminated body, and heated and cured;
[0009] e. Combining the modified prepreg body with the laminated body to obtain a composite body;
[0010] f. Place the composite body obtained in step e into a high-temperature furnace, heat it to 1500°C to 1800°C under argon (Ar) protection, keep it warm for 2 to 4 hours, cool it down in the furnace and take it out to obtain the high-temperature resistant lightweight composite ceramic heat shield.
[0011] The colloidal modifier is composed of the following components by weight percentage:
[0012]
[0013]
[0014] The components of the impregnation solution are as follows by weight percentage:
[0015]
[0016] The heating and curing steps of step c and step d are as follows: placing the modified prepreg blank or the laminated blank in a curing furnace, pressurizing it to 2.0MPa-3.0Mpa at room temperature, and then heating it in the curing furnace at a heating rate of 2.0°C / min-5.0°C / min, heating it to 180°C-200°C and keeping it warm and pressurized for 0.5-2.0 hours.
[0017] The modified prepreg blank and the laminated blank in step e are both planar and are pressed by a mold to form a planar, curved or shaped composite blank.
[0018] In the step e, the modified prepreg blank is wound in multiple layers on a hollow cylindrical mold of a winding machine, and then the laminated blank obtained in step d is wound to obtain a cylindrical composite blank.
[0019] The modifier in the modified prepreg body obtained in step c is 40% to 50% by weight of the modified prepreg body.
[0020] A reinforcement coating is applied on the surface of the composite body or the modified prepreg body of the cylindrical composite body.
[0021] The components of the strengthening coating are composed of the following by weight percentage:
[0022]
[0023] The modified prepreg blank is composed of 5 to 10 layers of modified prepreg, and the laminated blank is composed of 10 to 25 layers of modified prepreg and 10 to 25 layers of impregnated carbon fiber cloth alternately laminated.
[0024] The above technical solution disclosed in the present invention or the obtained ceramic heat insulation screen is obtained by modifying conventional glass fibers, and then undergoing specific process steps and high-temperature firing to obtain a large-sized overall flat, curved, special-shaped or overall thin-walled cylindrical heat insulation component (screen). After high-temperature sintering, the heat insulation component (screen) has a ceramic component and has excellent corrosion resistance. Under the protection of the ceramic component, the fiber filaments of the glass fiber cloth maintain their tensile strength and strength. At the same time, there is a certain amount of carbon component in the heat insulation component (screen), which makes the heat insulation component (screen) have high temperature resistance. Compared with the thermal field structure of C / C materials in the prior art, the heat insulation component (screen) of the present invention not only makes the heat insulation component (screen) larger, but also has high strength, especially greatly reduces the manufacturing cost and prolongs the service life of the heat insulation component (screen), and also has more economic benefits for the user and improves the use efficiency of the single crystal furnace. Specific implementation method:
[0025] The technical solutions of specific embodiments of the present invention are given in detail below. It should be noted that the description of the specific implementation methods of the present invention is to facilitate a comprehensive understanding of the technical content of the present invention, and should not be regarded as limiting the scope of protection of the claims of the present invention.
[0026] The technical solution of the specific embodiment of the present invention is: a. preparing a colloidal modifier for glass fiber cloth, immersing the glass fiber cloth in the colloidal modifier, taking it out, and baking it at 100°C to 110°C to obtain a modified prepreg of the glass fiber cloth; b. preparing an impregnation liquid for carbon fiber cloth, immersing the carbon fiber cloth in the impregnation liquid, taking it out, covering and sealing it with a high-temperature resistant plastic film, and heating it at 100°C to 120°C to obtain an impregnated carbon fiber cloth; c. layering multiple layers of the modified The modified prepreg cloth is stacked into a modified prepreg cloth blank, and heated and cured; d. The modified prepreg cloth and the impregnated carbon fiber cloth are alternately stacked to obtain a laminated blank, and heated and cured; e. The modified prepreg cloth blank and the laminated blank are combined into one to obtain a composite blank; f. The composite blank obtained in step e is placed in a high-temperature furnace, heated to 1500°C to 1800°C under the protection of argon (Ar), kept warm for 2 to 4 hours, and taken out after cooling with the furnace to obtain the high-temperature resistant lightweight composite ceramic heat insulation screen.
[0027] The colloidal state described in the above step a refers to the physical state of the modifier, which has a certain fluidity or plasticity and a certain viscosity. After the glass fiber cloth is immersed in the modifier, the modifier penetrates into the glass fiber cloth and adheres to the two surfaces of the glass fiber cloth. After baking, part of the volatile matter of the modifier escapes, which increases the adhesion to obtain a modified prepreg. After the carbon fiber cloth is immersed in the impregnation liquid, the impregnation liquid penetrates into the interior of the carbon fiber cloth. When heated at 100°C to 120°C, the plastic film seals and reduces the volatilization of volatiles, so that the impregnation liquid and the carbon fiber cloth are further fused and mutually penetrated, and the plasticity of the impregnation liquid is increased to obtain an impregnated carbon fiber cloth. The modified prepreg blank and the laminated blank in the above steps c and d need to be heated and cured in a heating furnace. The heating and curing can be performed separately in steps c and d, or they can be heated and cured at the same time to simplify the process and save energy. During the heating and curing, part of the volatile matter in the modified prepreg blank is volatilized and escaped, and at the same time, the various components of the colloidal modifier are further fused, and the volatile matter in the laminated blank is also escaped, and the various components of the impregnation liquid are also further fused and mutually penetrated. In the above step e, the modified prepreg blank and the laminated blank are combined into a composite blank. When combining, an external force is applied to the modified prepreg blank and the laminated blank to increase the bonding force between the two and promote the mutual fusion of the interface between the two, or the external force can be applied while heating to increase the degree of bonding. In step f, during the heating process and the heat preservation process at 1500°C to 1800°C, the colloidal modifier and the components of the impregnation liquid undergo complex high-temperature chemical reactions, and also undergo interfacial reactions with the fiber filaments of the glass fiber cloth and the carbon fiber filaments of the carbon fiber cloth. After experimental detection, the above-mentioned modifier generates a material with ceramic components as the main component, and the impregnation liquid generates a C / C material with part of the ceramic component and part of the carbon and carbon fiber combined. That is to say, the high-temperature resistant lightweight composite ceramic heat insulation screen of the present invention obtained after high-temperature firing is a ceramic material part composed of the modifier and the glass fiber cloth, and a part of the The ceramic-C / C material part is composed of the impregnation liquid and the carbon fiber cloth. In actual use, depending on the specific use environment and conditions, one side of the above-mentioned high-temperature resistant lightweight composite ceramic heat insulation screen can be set to contact the high-temperature heat source direction, and the above-mentioned heat insulation screen can be prepared into various configurations, such as flat plate, curved surface, semicircular or cylindrical. Not only does the heat insulation screen have extremely flexible adaptability, but more importantly, the ceramic part has excellent anti-oxidation or anti-silicon corrosion properties, and the ceramic-C / C material part has excellent heat resistance and good thermal conductivity. Therefore, the combination of the above two parts of the structure makes the heat insulation screen have excellent comprehensive performance.
[0028] The colloidal modifier is composed of the following components by weight percentage: 30-40% phenolic resin, 25-35% alcohol, 10-20% mullite powder, 5-10% carbon fiber powder, 10-20% silicon powder, 5-10% silicon carbide powder, 4-8% zirconium oxide powder and 5-15% short carbon fiber. The above components are fully mixed to form a colloidal modifier with certain rheological properties, which can adhere to the surface of glass fiber cloth. Due to the large proportion of phenolic resin and alcohol, the modifier has excellent permeability, so that the modifier is filled between glass fiber cloth, and even completely penetrates and fills between glass fiber filaments, so that the heat insulation screen after firing has excellent uniformity and basically consistent density, and the thermal stress is minimized when used at high temperature, reducing the generation of cracks. The proportion of the above components is obtained after a large number of tests, various performance tests and microscopic analysis. The particle size of mullite powder is less than 500 mesh, the particle size of silicon powder is less than 500 mesh, the particle size of silicon carbide powder is less than 1000 mesh and the particle size of zirconium oxide powder is less than 1000 mesh. The particle size of the above components is limited to make the components react effectively during high temperature firing, and at the same time make the particles of each component have a good fit with the surface of the aforementioned glass fiber cloth, that is, the particles of each component match the concave and convex surface of the glass fiber cloth, and there is a better stacking effect between the particles of each component, which can make the overall density higher and reduce the porosity and the existence of large pores. The other components in the above colloidal modifier can be purchased on the market. The carbon fiber powder is ground from pure carbon fiber, and the length of the short carbon fiber is generally 1 to 10 mm.
[0029] The impregnation liquid is composed of 70% phenolic resin, 22% graphite powder, 3% silicon powder, 3% silicon carbide powder and 2% silicon nitride powder by weight percentage. The above components are fully mixed to form an impregnation liquid with certain rheological properties, wherein the phenolic resin and the particle surfaces of other components interpenetrate each other and cover the particles of each component and the carbon fiber filaments of the carbon fiber cloth. During the high-temperature firing process, part of the phenolic resin is carbonized, and part of it reacts chemically with other components. At the same time, complex chemical reactions also occur between the components. The carbonized phenolic resin and the carbon fiber cloth generate C / C material, and the impregnation liquid and other components generate part of carbon material and part of ceramic material to form C / C material-C / ceramic material.
[0030] The heating and curing steps of step c and step d are as follows: placing the modified prepreg blank or the laminated blank in a curing furnace, pressurizing it to 2.0MPa-3.0MPa at room temperature, and then heating it in the curing furnace at a heating rate of 2.0℃ / min-5.0℃ / min, heating it to 180℃-200℃ and keeping it at this temperature for 0.5-2.0 hours. In the above-mentioned heating and curing, the heating rate is controlled so that the volatile matter in the blank gradually evaporates, and under the action of pressure, the blank is gradually or has sufficient time to be compressed. Keeping it at this temperature and pressure can not only compress the blank as much as possible, but also allow the components inside the blank to have sufficient time to fuse and penetrate.
[0031] The modified prepreg blank and the laminated blank in step e are both planar, and are pressed into a planar, curved or shaped composite blank by a mold. The specific shape of the composite blank is selected from different molds according to specific needs. The edge of the composite blank has a concave-convex part or a buckle part, so that the two can be easily connected after high-temperature firing to form a larger heat shield or a heat shield with a more complex shape. Alternatively, in step e, the modified prepreg blank is wound on the hollow cylindrical mold of the winding machine for multiple layers, and then wound with the laminated blank obtained in step d to obtain a cylindrical composite blank. The cylindrical heat shield obtained by high-temperature firing of the cylindrical composite blank is particularly suitable as a crucible side used in a single crystal silicon pulling furnace.
[0032] In order to further improve the corrosion resistance of the heat insulation screen, the modifier in the modified prepreg blank obtained in step c is 40% to 50% by weight of the modified prepreg blank; this can make the thickness of the colloidal modifier between adjacent glass fiber cloths close to or equal to the thickness of the glass fiber cloth, or the ceramic material between adjacent glass fiber cloths after high-temperature firing has sufficient thickness, so that the heat insulation screen has good corrosion resistance and oxidation resistance, and can also provide sufficient protection for the core of the glass fiber filaments to ensure the strength performance of the heat insulation screen.
[0033] In order to further improve the comprehensive performance or corrosion resistance of the heat insulation shield, a strengthening coating is coated on the surface of the composite body or the modified prepreg body of the tubular composite body. After high-temperature firing, the strengthening coating forms a ceramic material layer with silicon as the main component, which has good corrosion resistance. When the tubular heat insulation shield is used as the above-mentioned crucible side, the above-mentioned ceramic material with silicon as the main component basically does not react with the silicon of the quartz crucible, and will not cause the quartz crucible to desiliconize. The components of the above-mentioned strengthening coating are composed of 55% silicone resin, 30% silicon powder, 3% silicon nitride powder, 2% silicon carbide powder and 10% zircon powder by weight percentage; wherein the particle size of the silicon powder is 20μm to 80μm, and the purity is ≥99.9%, the particle size of the silicon nitride powder is 30μm to 100μm, and the purity is ≥99.5%, the particle size of the silicon carbide powder is 3μm to 100μm, and the purity is ≥99.5%, the particle size of the zircon powder is 3μm to 20μm, and the purity is ≥99.0%, the product number of the silicone resin is SH-9601, and the solid content is 50 to 55%.
[0034] In order to ensure that the heat shield has good comprehensive performance, the modified prepreg blank is composed of 5 to 10 layers of modified prepreg, and the laminated blank is composed of 10 to 25 layers of modified prepreg and 10 to 25 layers of impregnated carbon fiber cloth alternately laminated. The heat shield of the above structure has a ceramic component-based part with sufficient oxidation resistance and corrosion resistance, and the composite material composed of C / C material-C / ceramic material and ceramic material formed by high-temperature firing of the laminated blank has good strength, good thermal conductivity and good corrosion resistance, and greatly reduces the use of expensive carbon fiber cloth, which greatly reduces the preparation cost of the heat shield and greatly increases the service life.
Claims
1. A method for preparing a high temperature resistant lightweight composite ceramic heat insulation screen, characterized in that: The steps of the preparation method of the heat shield are as follows: a. Preparation of a colloidal modifier for glass fiber cloth, the glass fiber cloth is immersed in the colloidal modifier and then taken out, and baked at 100 ℃ ~ 110 ℃ to obtain a modified prepreg of glass fiber cloth; The colloidal modifier is composed of the following components by weight percentage: 30-40% phenolic resin, 25-35% alcohol, 10-20% mullite powder, 5-10% carbon fiber powder, 10-20% silicon powder, 5-10% silicon carbide powder, 4-8% zirconium oxide powder, 5-15% short carbon fiber; b. preparing an impregnation liquid for a carbon fiber cloth, impregnating the carbon fiber cloth in the impregnation liquid, taking it out, covering it with a high temperature resistant plastic film, and heating it at 100 ℃ to 120 ℃ to obtain an impregnated carbon fiber cloth; The components of the impregnation solution are as follows by weight percentage: 70% phenolic resin, 22% graphite powder, 3% silicon powder, 3% silicon carbide powder, 2% silicon nitride powder; c. Laminating multiple layers of the modified prepreg to form a modified prepreg blank, and heating and curing the blank; d. The modified prepreg and the impregnated carbon fiber cloth are alternately laminated to obtain a laminated body, and heated and cured; e. Combining the modified prepreg body with the laminated body to obtain a composite body; f. Place the composite body obtained in step e into a high-temperature furnace, heat it to 1500°C to 1800°C under argon (Ar) protection, keep it warm for 2 to 4 hours, cool it down in the furnace and take it out to obtain the high-temperature resistant lightweight composite ceramic heat shield.
2. The method for preparing the high temperature resistant lightweight composite ceramic heat insulation screen according to claim 1, characterized in that: The heating and curing steps of step c and step d are as follows: placing the modified prepreg blank or the laminated blank in a curing furnace, pressurizing it to 2.0MPa-3.0Mpa at room temperature, and then heating it in the curing furnace at a heating rate of 2.0°C / min-5.0°C / min, heating it to 180°C-200°C and keeping it warm and pressurized for 0.5-2.0 hours.
3. The method for preparing the high temperature resistant lightweight composite ceramic heat insulation screen according to claim 2, characterized in that: The modified prepreg blank and the laminated blank in step e are both planar and are pressed by a mold to form a planar, curved or shaped composite blank.
4. The method for preparing the high temperature resistant lightweight composite ceramic heat insulation screen according to claim 2, characterized in that: In step e, the modified prepreg blank is wound in multiple layers on a hollow cylindrical mold of a winding machine, and then the laminated blank obtained in step d is wound to obtain a cylindrical composite blank.
5. The method for preparing the high temperature resistant lightweight composite ceramic heat insulation screen according to claim 3 or 4, characterized in that: The modifier in the modified prepreg body obtained in step c accounts for 40% to 50% of the weight of the modified prepreg body by weight percentage.
6. The method for preparing the high temperature resistant lightweight composite ceramic heat shield according to claim 5, characterized in that: A reinforcement coating is applied on the surface of the composite body or the modified prepreg body of the cylindrical composite body.
7. The method for preparing the high temperature resistant lightweight composite ceramic heat insulation screen according to claim 6, characterized in that: The components of the strengthening coating are composed of the following by weight percentage: 55% silicone resin, 30% silicon powder, 3% silicon carbide powder, 2% silicon carbide powder, 10% zircon powder.
8. The method for preparing the high temperature resistant lightweight composite ceramic heat insulation screen according to claim 7, characterized in that: The modified prepreg blank is composed of 5 to 10 layers of modified prepreg, and the laminated blank is composed of 10 to 25 layers of modified prepreg and 10 to 25 layers of impregnated carbon fiber cloth alternately laminated.
Citation Information
Patent Citations
Large-scale integral thin-wall carbon / ceramic composite material gas limiting cylinder and preparation method thereof
CN111039685A
Coated carbon-carbon composite material crucible and preparation method thereof
CN112759423A